Misinformation in the digital age : an American infodemic - Stephens, Monica; Poon, Jessie P.; Tan, Gordon K. (The International Geographical Union series on contemporary geographies, 2023)
"Using a geographic lens to examine the adoption and dissemination of, and attention to 'fake news', this timely and important book explores how misinformation in the digital age calls attention to the multiple geographic dimensions of online fictions, conspiracy theories and political disinformation. Chapters delve into how social and digital media have rescaled and disrupted relations of trust and authority in the (mis)information age. The book draws on quantitative data and qualitative cases to shed light on the geographies of misinformation, covering urban legends, political rumors, information weaponization, and Climategate, as well as trade and financial fictions. The book explores in depth climate change misinformation, conspiracy theories and other critical contemporary events such as Pizzagate, Russian-led overseas political interference campaigns, and Cambridge Analytica. Geography and environmental studies scholars will benefit from the analysis of the denial of global climate change and geographic lens the book uses. It will also be an important read for practitioners and policy makers looking for a helpful reference summarizing interdisciplinary work on misinformation in accessible prose"--